The Impact of Academic Supervision, Work Environment, and Principal Leadership on the Performance of Elementary School Teachers - Jamil, Jamil; Makkasau, Andi; Syawaluddin, Ahmad (FKIP Universitas Lampung, 2025)
The Impact of Academic Supervision, Work Environment, and Principal Leadership on the Performance of Elementary School Teachers. Objective: The aim of this investigation is to evaluate the impact of academic supervision, work environment, and principal leadership on the performance of elementary school teachers in Lembang District, Pinrang Regency. The study's primary objective is to determine the degree to which these variables, both individually and collectively, influence the quality of teacher performance. Methods: This investigation employs a survey methodology in conjunction with a quantitative methodology. The population consists of 42 instructors from four public elementary schools in Lembang District: SDN 150, 152, 153, and 200 Pinrang. A proportional random sampling technique was employed to select a sample of 30 instructors. The research instrument is a questionnaire that has been extensively evaluated for its validity and reliability in order to assess the variables of academic supervision, teacher performance, work environment, and leadership. SPSS version 25 was employed to conduct data analysis through multiple linear regression. Findings: Regression analysis results demonstrated that teacher performance was substantially influenced by principal leadership, academic supervision, and the work environment (R² = 0.707). Academic supervision was the most significant variable influencing teacher performance (β = 0.619), with work environment (β = 0.345) and principal leadership (β = 0.173) following in that order. The regression assumptions, including absence of multicollinearity, linearity, and normality, were satisfied by all variables. Conclusion: This investigation affirms that the quality of principal leadership, the establishment of a supportive work environment, and the implementation of appropriate academic supervision significantly impact teacher performance enhancement. This finding suggests that it is necessary to enhance the quality of basic education by bolstering the capacity of principals, work environment management strategies, and supervision systems. Keywords: principal leadership, work environment, academic supervision.